Triple regional anaesthesia technique in resection of left pleuropulmonary sarcoma and left subclavian artery bypass. Issue 1 (22nd April 2019) - Dillon, D.; Johnston, D. F.
Summary: A 28‐year‐old woman presented for excision of a left‐sided pleuropulmonary sarcoma which was adherent to her left subclavian artery and mediastinum. A left upper lobe wedge resection was performed via a median sternotomy and a left carotid artery‐to‐left subclavian artery bypass was performed through a left supraclavicular incision. We report on a triple regional anaesthesia technique to provide postoperative analgesia. We inserted bilateral transverse thoracic plane catheters for continuous local anaesthetic infusion and performed bilateral subcostal transversus abdominus plane blocks for drain site analgesia. A left superficial cervical plexus block was performed to cover pain from the supraclavicular incision. Anteromedial chest wall blocks are an emerging analgesic technique for sternotomy and were successfully used as part of a combined regional anaesthetic for a patient undergoing complex thoracic surgery.